Identification and significance of unsaturated archaeal tetraether lipids in marine sediments. (3rd April 2014) - Zhu, Chun; Yoshinaga, Marcos Y.; Peters, Carl A.; Liu, Xiao‐Lei; Elvert, Marcus; Hinrichs, Kai‐Uwe
<x xml:space="preserve">Abstract</x> RATIONALE Studies of archaeal glycerol dibiphytanyl glycerol tetraethers (GDGTs) in the environment and cultures have exclusively focused on compounds with fully saturated alkyl moieties. Here we report a number of novel unsaturated GDGTs (uns‐GDGTs) whose alkyl chains contain up to six double bonds and zero to two cyclopentyl moieties. METHODS The identification of these lipids was achieved via comparison of lipid distribution before and after hydrogenation, characteristic retention time patterns, and diagnostic ions using liquid chromatography/tandem mass spectrometry (LC/MS/MS), and ether cleavage products using gas chromatography/mass spectrometry (GC/MS). Isomerism resulting from different unsaturation patterns in the alkyl moieties was observed and specific positions of double bonds in the biphytene and biphytadiene moieties were tentatively assigned. RESULTS Uns‐GDGTs were detected in sediment and microbial mat samples as both core lipids (CLs) and intact polar lipids (IPLs) associated with mono‐ or diglycosyl or phosphatidylglycerol headgroups. However, these lipids were overlooked in past investigations because conventional methods for archaeal lipid analysis are unsuitable for uns‐GDGTs. Samples from distinct marine environments (Black Sea, Cariaco Basin, Discovery Basin, Eastern Mediterranean Sea, upwelling area off NW Africa, and seep sites off Crimea and Pakistan) were screened for uns‐GDGTs using a new LC/MS protocol. The results show that uns‐GDGTs contribute significantly to the archaeal lipid pool in anoxic methane‐rich environments (Black Sea, Cariaco Basin, and both seep sites) but they were barely detected in the oxic or hypersaline settings. CONCLUSIONS The characteristic distribution of uns‐GDGTs implies that they are attractive targets for future studies aiming at the chemotaxonomy of uncultivated archaea and regulation of uns‐GDGT biosynthesis. Copyright © 2014 John Wiley & Sons, Ltd.